Sintering effect on mechanical properties of composites made of bovine hydroxyapatite (BHA) and commercial inert glass (CIG) - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2007)
Composite biomaterials of calcinated bovine bone derived hydroxyapatite (HA) doped with 5 and 10 wt% commercial inert glass (CIG) were prepared by sintering. The production of HA from natural sources satisfies economic and time-saving aims, while the use of CIGs is directed by economic and ecological aspects. The produced composites were subjected to scanning electron microscopy (SEM) and X-ray diffraction analysis. Measurements of compression strength, microhardness, and density were also carried out. The experimental results and their discussion showed that the type and the composition of incorporated glass are of crucial importance. Consequently, provided that ail optimum amount of glass is incorporated, the resultant materials call exhibit good values of compression strength and microhardness and hence they can be suggested for potential use in load-bearing biomedical applications.
Keywords: hydroxyapatite; bioinert glass; sintering; economy; mechanical properties microstructure